Analysis of The Use Of Social Media Marketing on Customer Loyalty Through Brand Trust on Taxpayers In Samsat Binjai - Siti Nurmaizar; Elfitra Desy Surya; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This study aims to test and analyze the influence of entertainment and electronic word of mouth entertainment and electronic word of mouth have a positive and significant effect on brand trust. Entertainment and electronic word of mouth positively and significantly affect customer loyalty at the Samsat Binjai office. Likewise, entertainment and electronic word of mouth have a positive and significant effect on customer loyalty mediated by brand trust. Entertainment has a significant influence on customer loyalty, especially when mediated by brand trust. The research method is quantitative. The population in this study amounted to 170 and by using the slovin formula, a sample of 63 respondents was obtained. The data processing method uses SMART PLS. The results of this study show that entertainment and electronic word of mouth entertainment and electronic word of mouth have a positive and significant effect on brand trust. Entertainment and electronic word of mouth positively and significantly affect customer loyalty at the Samsat Binjai office. Likewise, entertainment and electronic word of mouth have a positive and significant effect on customer loyalty mediated by brand trust.